Antimalarial chemoprophylaxis for forest goers in southeast Asia: an open-label, individually randomised controlled trial. Issue 1 (January 2023) - Tripura, Rupam; von Seidlein, Lorenz; Sovannaroth, Siv; Peto, Thomas J; Callery, James J; Sokha, Meas; Ean, Mom; Heng, Chhouen; Conradis-Jansen, Franca; Madmanee, Wanassanan; Peerawaranun, Pimnara; Waithira, Naomi; et al.
Summary: Background: Malaria in the eastern Greater Mekong subregion has declined to historic lows. Countries in the Greater Mekong subregion are accelerating malaria elimination in the context of increasing antimalarial drug resistance. Infections are now increasingly concentrated in remote, forested foci. No intervention has yet shown satisfactory efficacy against forest-acquired malaria. The aim of this study was to assess the efficacy of malaria chemoprophylaxis among forest goers in Cambodia. Methods: We conducted an open-label, individually randomised controlled trial in Cambodia, which recruited participants aged 16–65 years staying overnight in forests. Participants were randomly allocated 1:1 to antimalarial chemoprophylaxis, a 3-day course of twice-daily artemether–lumefantrine followed by the same daily dosing once a week while travelling in the forest and for a further 4 weeks after leaving the forest (four tablets per dose; 20 mg of artemether and 120 mg of lumefantrine per tablet), or a multivitamin with no antimalarial activity. Allocations were done according to a computer-generated randomisation schedule, and randomisation was in permuted blocks of size ten and stratified by village. Investigators and participants were not masked to drug allocation, but laboratory investigations were done without knowledge of allocation. The primary outcome was a composite endpoint of either clinical malaria with any Plasmodium species within 1–28, 29–56, or 57–84 days, or subclinical infection detected by PCR on days 28, 56, or 84 using complete-case analysis of the intention-to-treat population. Adherence to study drug was assessed primarily by self-reporting during follow-up visits. Adverse events were assessed in the intention-to-treat population as a secondary endpoint from self-reporting at any time, plus a physical examination and symptom questionnaire at follow-up. This trial is registered at ClinicalTrials.gov (NCT04041973 ) and is complete. Findings: Between March 11 and Nov 20, 2020, 1480 individuals were enrolled, of whom 738 were randomly assigned to artemether–lumefantrine and 742 to the multivitamin. 713 participants in the artemether–lumefantrine group and 714 in the multivitamin group had a PCR result or confirmed clinical malaria by rapid diagnostic test during follow-up. During follow-up, 19 (3%, 95% CI 2–4) of 713 participants had parasitaemia or clinical malaria in the artemether–lumefantrine group and 123 (17%, 15–20) of 714 in the multivitamin group (absolute risk difference 15%, 95% CI 12–18; p<0·0001). During follow-up, there were 166 malaria episodes caused by Plasmodium vivax, 14 by Plasmodium falciparum, and five with other or mixed species infections. The numbers of participants with P vivax were 18 (3%, 95% CI 2–4) in the artemether–lumefantrine group versus 112 (16%, 13–19) in the multivitamin group (absolute risk difference 13%, 95% CI 10–16; p<0·0001). The numbers of participants with P falciparum were two (0·3%, 95% CI 0·03–1·01) in the artemether–lumefantrine group versus 12 (1·7%, 0·9–2·9) in the multivitamin group (absolute risk difference 1·4%, 95% CI 0·4–2·4; p=0·013). Overall reported adherence to the full course of medication was 97% (95% CI 96–98; 1797 completed courses out of 1854 courses started) in the artemether–lumefantrine group and 98% (97–98; 1842 completed courses in 1885 courses started) in the multivitamin group. Overall prevalence of adverse events was 1·9% (355 events in 18 806 doses) in the artemether–lumefantrine group and 1·1% (207 events in 19 132 doses) in the multivitamin group (p<0·0001). Interpretation: Antimalarial chemoprophylaxis with artemether–lumefantrine was acceptable and well tolerated and substantially reduced the risk of malaria. Malaria chemoprophylaxis among high-risk groups such as forest workers could be a valuable tool for accelerating elimination in the Greater Mekong subregion. Funding: The Global Fund to Fight AIDS, Tuberculosis and Malaria; Wellcome Trust.